PERANAN LEMBAGA PEMBERDAYAAN MASYARKAT DALAM MEMBANTU KEPALA DESA MENYUSUN RENCANA PEMBANGUNAN DESA - Syaprianto, Syaprianto; Prihatin, Panca Setyo (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
This study aims to look at the role of the Institute for Community Empowerment In Assisting the Head of the Village Development Plan Rural, Theory used in this research is the Role According Soerjono Soekanto The role is covering the norm - norms associated with the position or one's place in society. The role in this sense is a set of rules - the rules that guide the person in social life and then Indicators used in this study is based on the regional Regulation of Rokan Hulu District No. 13 Year 2007 on Community Institutions in Article 8, namely Prepare development plans in a participatory manner, Implement, Control, utilize and develop participatory Development and Promote and develop participation, gotong-royong and governmental organizations. The type of research is quantitative descriptive as well as study population, namely the Village Head fullness of West Sei Rokan Jaya subdistrict Fullness of Rokan Hulu, the village secretary, BPD, LPM, affairs chief General, Head of government affairs, Chief in charge of Finance, Head of Hamlet, RW, RT and head of Family Fullness West Sei Rokan Jaya determined by census techniques and purposive sampling and simple random sampling of the type of data collection is primary data and secondary data, engineering data collection using questionnaires, interviews and observations, then the data were analyzed descriptively using quantitative methods descriptively, based on the results of the analysis of the role of the Institute for Community Empowerment In Helping the Village Head Making Plans Rural Development (Study village Fullness West Sei Rokan Jaya subdistrict Fullness of Rokan Hulu Year (2011) assessed Enough to Succeed, Expected to Village Government Fullness West Sei Rokan for more increase community empowerment village so that people of helplessness and welfare increases.